Ethical journalism vs digital journalism: ¿Las dos caras de la misma moneda? - Jiménez Vinuesa, Chal; Nicolás-Sans, Rubén (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
In journalism, ethics is also essential for the citizen to receive quality information to live in a free democracy. The functions of journalism are diverse, to inform, investigate, analyze, create social ties, in addition to the great social work it represents discovering or denouncing what is hidden or the information that citizens need to choose an adequate government. Based on the previous points, the current study explores the concept of digital journalism through a bibliographic review, while addressing different aspects of the current state of the journalistic profession.